LITERATURE REVIEW KAJIAN ETIS PENGHENTIAN TERAPI MEDIS DALAM PERSPEKTIF PRINSIP MORAL BIOETIKA - David Simanjuntak; Meivy Isnoviana (PT. Hasba Edukasi Mandiri, 2026)
The enactment of Law Number 17 of 2023 concerning Health marks a major transformation in Indonesia's medical regulation, particularly regarding the reconstruction of professional organizations' authority and legal protection mechanisms for medical personnel. The dynamics of the legal relationship between doctors and patients often trigger complex medical disputes, necessitating clarity on the boundaries of professional responsibility and effective resolution channels. Methods: This research utilizes a normative legal research method with a statutory approach and literature review. Secondary data were analyzed qualitatively to evaluate the impact of the new regulation on medical practice and professional legal protection. Results: Findings indicate that the legal relationship in healthcare services is contractual, where medical failure is more accurately viewed as a breach of contract regarding standard operating procedures rather than a criminal offense. Although the 2023 Health Law attempts to integrate the system, synchronization of derivative regulations is still required to prevent the criminalization of doctors. Dispute resolution through professional channels (MKDKI) is considered more effective in maintaining confidentiality and ethics, yet synergy with litigation channels remains necessary to ensure fair compensation for patients without neglecting protection for doctors.